GENE-37. ATRX INACTIVATION DISRUPTS GLOBAL HETEROCHROMATIN LANDSCAPES AND ALTERS DISEASE-RELEVANT TRANSCRIPTIONAL ACTIVITY. (5th November 2018) - Danussi, Carla; Singh, Anand K; Fischer, Grant; Picketts, David J; Kannan, Kasthuri; Rai, Kunal; Huse, Jason T
Abstract: Diffusely infiltrating gliomas feature loss-of function mutations in the SWI/SNF chromatin remodeler gene ATRX as defining molecular alterations delineating major adult and pediatric disease subtypes. So far, ATRX inactivation in cancer has been mainly correlated with alternative lengthening of telomeres, however, we recently reported that Atrx deficiency drives glioma-relevant phenotypes, such as increased motility and astrocytic differentiation profiles, by directly modulating epigenomic landscapes and the corresponding transcriptional profiles in glioma cells of origin. In particular, Atrx deficiency was associated with disruptions in H3.3 histone content at key genetic loci. To further understand the downstream epigenomic dysfunction induced by ATRX deficiency, we compared genome-wide chromatin-state maps of Atrx+ and Atrx- primary murine neuroepithelial progenitors (mNPCs). This ChIP–seq analysis revealed major differences in the localization of heterochromatin repressive marks H3K9me3 and H3K27me3. Specifically, we identified peculiar locations in the genome displaying H3K9me3 depletion and gain of H3K27me3 upon Atrx inactivation. Interestingly, these regions were flanked by Atrx binding sites and perfectly co-localized with Lamina-Associated Domains (LADs). LADs are widely involved in the control of gene expression programs during lineage commitment and terminal differentiation; typically they have a cell-specific distribution and are very dynamic during differentiation stages. Gene Set Enrichment Analysis confirmed that the genes corresponding to newly formed LADs in mNPC-to-astrocyte differentiation are significantly enriched for genes down-regulated in Atrx deficient mNPCs and belonging to Gene Ontology categories such as cell cycle, chromosome organization and DNA damage. On the other hand, genes corresponding to decreased LAD association are enriched for up-regulated genes in Atrx- mNPCs and for regulation of differentiation, adhesion and cell death. These data are in perfect agreement with our previously described glioma-relevant phenotypes associated with Atrx deficiency and indicate a novel role of Atrx in regulating the spatial organization of heterochromatin and its underlying transcriptional activity.